Humanism, Universities, and Jesuit Education in Late Renaissance Italy - Grendler, Paul F., author.
1 online resource.
Keywords: This book contains twenty essays on Italian Renaissance humanism, universities, and Jesuit education in three equal parts. The book defines Renaissance humanism, then studies biblical humanism, humanistic education in Venice, the pioneering historian of humanism Georg Voigt, and Paul Oskar Kristeller. The middle section discusses Italian universities, the sports played by university students, a famous law professor, and the controversy over the immortality of the soul. The last section analyses Jesuit education: the culture of the Jesuit teacher, the philosophy curriculum, attitudes toward Erasmus and Juan Luis Vives, and the education of a cardinal. This volume collects Paul Grendler's most recent research (published and unpublished), offering to the reader a broad fresco on a complex and crucial age in the history of education.